Development of Illustrator Software Assisted Clothes Design Learning E-Module for Vocational School Fashion Design Program (Universitas Negeri Semarang, 2022)
E-module learning media is learning media that provides innovation which can include videos, animations, and images in it using a Flipbook Maker application. The e-module learning media in this study were compiled using Adobe Illustrator software, while the purpose of creating e-module media is to help students better understand the contents of the material in it. The research aims to develop an e-module for learning clothes design assisted by the illustrator application software for eleventh grade students of Fashion Design Program at SMK Negeri 3 Kudus to improve learning outcomes.The data analysis used in the present study was to determine the feasibility level of the interactive clothes design e-module; to determine the level of practicality of the interactive clothes design e-module, and to determine the effectiveness of the e-module to improve learning outcomes. Based on the feasibility test and the effectiveness test of the clothes design e-module which was developed and the responses given by media experts and material experts, namely senior teachers and academics (lecturers), the e-module obtained very feasible response criteria, from the practicality test, it obtained very practical criteria , and from the effectiveness test in the experimental class, the criteria are quite effective and significantly used by students to improve student learning outcomes.